SINGLE NUCLEOTIDE POLYMORPHISMS OF LIPOPROTEIN LIPASE GENE AND ITS ASSOCIATION WITH MARBLING QUALITY IN LOCAL SHEEPS - Hidayati, H.; Sumantri, C.; Noor, R. R.; Priyanto, R.; Rahayu, S. (Diponegoro University, 2015)
Lipoprotein lipase (LPL) is a key enzyme that plays in metabolism and transport lipoprotein andtherefore has an influence on blood triglyceride levels. LPL controls triacylglycerol partitioning betweenadipose tissue and muscle that increases fat storage or provides energy in the form of fatty acids formuscle growth. The research was aimed to explore Single Nucleotide Polymorphisms of LPL gene andto associate SNP with marbling quality. A total of 66 genomic DNAs consisted of sumatera thin-tail edsheep (50 heads) and garut sheep (16 heads) were used in this study. Polymerase Chain Reaction wasused to amplify genomic DNA and direct sequencing method was to identify polymorphism sequences.The sequences were analyzed with Bio Edit and MEGA 5.2. The BLAST sequence was obtained fromgene bank X.68308.1. The association between the genotype and marbling quality was analyze by oneway ANOVA and further between mean differences were tested using least sgnificant difference. Theresults showed that 3 novel SNPs i.e. insertion g.26>C; insertion g.27> G and c.192T>C on garut sheepand a SNP insertion g.26>C/G on sumatera thin-tail ed sheep. The diversity of LPL gene at c.192T>Cwas associated with heneicosanoic acid, whereas TT genotype (0.04%) was higher than CC (0.03%) andCT (0.02%).